1999
DOI: 10.1111/j.1751-3928.1999.tb00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earth Elements as an Indicator to Origins of Skarn Deposits: Examples of the Kamioka Zn‐Pb and Yoshiwara‐Sannotake Cu(–Fe) Deposits in Japan

Abstract: : Systematic data of rare earth elements (REEs) are presented in order to put some constraints on the origin of hydrothermal fluids responsible for two contrastive skarn deposits in Japan; the Kamioka Zn‐Pb and Yoshiwara‐Sannotake Cu(‐Fe) deposits. Carbon and oxygen isotopic studies have demonstrated that the hydrothermal fluids responsible for the Kamioka Zn‐Pb deposits are of meteoric water origin whereas those for the Yoshiwara‐Sannotake Cu(‐Fe) deposits are of magmatic water origin. The REE abundances of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 41 publications
(62 reference statements)
2
11
0
Order By: Relevance
“…In contrast, the skarns exhibit slight enrichment of Eu with increasing total REE concentrations relative to the dolomitic marble, implying a contribution of magmatic fluid derived from granitoids during the skarn formation (cf. Kato, 2008).…”
Section: Conditions For Formation Of Skarnsmentioning
confidence: 95%
“…In contrast, the skarns exhibit slight enrichment of Eu with increasing total REE concentrations relative to the dolomitic marble, implying a contribution of magmatic fluid derived from granitoids during the skarn formation (cf. Kato, 2008).…”
Section: Conditions For Formation Of Skarnsmentioning
confidence: 95%
“…Irrespective of the nature of associated igneous activity, it is also plausible that the tin content of garnet from the deposits is low, because they are formed by hydrothermal solutions of meteoric water origin (Shimazaki and Kusakabe, 1990). Some examples, however, such as the Kamaishi and Sannotake deposits, are confirmed to have formed by solutions of magmatic water origin (Morishita and Matsuhisa, 1983;Kato, 1999), and the tin content of garnets from these deposits is clearly low as shown in Table 2.…”
Section: Sn Contentmentioning
confidence: 99%
“…The oxygen isotopic compositions of the fluids responsible for the Kamioka deposits were estimated to be as low as -4 to +3‰ (SMOW), demonstrating that the deposits were derived from the hydrothermal fluids of meteoric water origin (Shimazaki et al, 1986;Shimazaki and Kusakabe, 1990). Moreover, the REE concentrations of clinopyroxene, garnet, and calcite formed as hydrothermal products are considerably low relative to those of original crystalline limestone, indicating no significant contribution of magmatic fluids during the formation of skarn and ore (Kato, 1991a(Kato, , 1999. Three major deposits, Mozumi, Maruyama, and Tochibora, are composed of 10 to nearly 50 discrete massive orebodies.…”
Section: Geological Setting and Ore Depositsmentioning
confidence: 99%
“…As to the origin of the ore-forming fluids responsible for the Kamioka deposits, Shimazaki and his colleagues have demonstrated that the fluids were of meteoric water origin based on oxygen isotopes of calcite, clinopyroxene, and quartz (e.g., Shimazaki et al, 1986;Shimazaki and Kusakabe, 1990). Moreover, rare earth element (REE) data of skarn and ore calcite also have suggested that the origin of metals in the hydrothermal fluids was not magmatic (Kato, 1991a(Kato, , 1999. The transportation of the fluids has been discussed in some papers (e.g., Kawasaki et al, 1985;Sakurai et al, 1993;Hirokawa et al, 1995).…”
Section: Introductionmentioning
confidence: 99%